Analysing Coloured Petri Nets by the Occurrence Graph Method - Jørgensen, Jens Bæk (DAIMI Report Series, 1997)
This paper provides an overview og the work done for the author's PhD thesis. The research area of Coloured Petri Nets is introduced, and the available analysis methods are presented. The occurrence graph method, which is the main subject of this thesis, is described in more detail. Summaries of the six papers which, together with this overview, comprise the thesis are given, and the contributions are discussed. A large portion of this overview is dedicated to a description of related work. The aim is twofold: First, to survey pertinent results within the research areas of -- in increasing generality -- Coloured Petri Nets, High-level Petri Nets, and formalisms for modelling and analysis of parallel and distributed systems. Second, to put the results obtained in this thesis in a wider perspective by comparing them with important related work.